Review of solid state transfer switch on requirements, standards, topologies, control, and switching mechanisms: Issues and challenges - Faisal M.; Hannan M.A.; Ker P.J.; Bin Abd Rahman M.S.; Mollik M.S.; Mansur M.B. (MDPI AG, 2023)
Large-scale industrial loads, sensitive loads, and electrical power distribution systems suffer from power quality issues such as voltage interruptions, flickering, and sags which can cause a significant financial loss. The semiconductor based solid-state transfer switch (SSTS) can utilize the dual power feeders to protect the loads against these power disturbance issues. Conventional SSTS often requires more than quarter cycles to complete the transfer process because of load dependent commutation. Numerous researchers proposed the improved SSTS with impulse commutated circuit, which can reduce the transfer time and provide better ride-through capability against voltage sags. However, the SSTS specification depends on the application types and design procedure. Recently, hybrid SSTS has been introduced by the researchers to overcome all these issues. It has been investigated that not much papers are available in literature so far to aggregate all these issues. Therefore, towards the novel contribution of research, this review critically described the requirements, standards, and specifications of SSTS; control and switching mechanisms; and application of SSTS as single or hybrid topology, to give a comprehensive idea to the future researchers about the design of SSTS for a specific application. This paper also contributes to analyzing the key issues related to the SSTS applications, which can provide an easy control strategy and reduce the transfer time significantly. Overall, this research will strengthen the efforts of the researchers and industrialists to select, develop, and design the appropriate SSTS for a particular application. 2020 by the authors. Licensee MDPI, Basel, Switzerland.